Digital Transformation and Business Incubation on SME Performance in Indonesia - Alif Ringga Persada; Hari Mulyadi; A. Jajang Warya Mahri; Chairul Furqon (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In this rapidly evolving digital era, digital transformation and business incubation have been identified as key determinants in driving improved performance SMEs in Indonesia. A quantitative study, using an explanatory approach, specifically investigated how these two aspects affect 200 SMEs in Indonesia that have actively adopted digital technology and participated in incubation programs. The information for the study was collected through an extensive survey and analyzed in depth using multiple linear regression methods. The findings suggest that digital transformation possesses a significant and positive impact on SME business performance. This impact is mainly manifested through the utilization of strategies such as the use of e-commerce, the implementation of an efficient digital management system, and the optimization of social media, which collectively contribute to increased operational efficiency and expanded market reach. Furthermore, incubation programs have also been shown to play a crucial role in improving performance, by providing relevant training, expert mentoring, and vital access to business networks. Overall, this study confirms that the synergy between digital transformation and business incubation substantially improves SME performance.